Avaliação da atividade antileishmania de produtos naturais isolados de phyllanthus acuminatus e de hyptis macrostachys - Dias, Cínthia Nóbrega de Sousa (2014)
Leishmaniasis is a complex of inserted parasitic diseases in the group of neglected tropical diseases. The drugs used primarily in the treatment of leishmaniasis are pentavalent antimonials and amphotericin B. However, these drugs are associated with serious side effects. Therefore, it is necessary to search for new antileishmanial drugs. In this context natural products are a source of new active molecules. This study, it was investigated the antileishmanial activity of the ethanol extract of Phyllanthus acuminatus and Justicidin B, lignan obtained from this plant and the ethanol extract, the dichloromethane phase and Hyptenolide obtained from Hyptis macrostachys in vitro experimental models. All samples assessed showed antileishmanial activity, initially demonstrated by inhibition of growth of L. amazonensis promastigotes in logarithmic growth phase. The concentration that inhibits 50% of growth (IC50) for the tested substances was 35.58 μg /mL for the ethanolic extract of P. acuminatus, 12.51 μg/mL for Justicidin B; 280.69 μg/mL for the ethanol extract of H. macrostachys, 55.3 μg/mL for dichloromethane phase of H. macrostachys and 22.67 μg/mL for Hyptenolide. These samples were also evaluated for cytotoxicity in murine peritoneal macrophages of swiss mice, which resulted in the measurement of the cytotoxic concentration for 50% macrophages (CC50), which were 39.62 μg/mL for the ethanolic extract of P. acuminatus, 58.56 μg/ml for Justicidin B; 121,36 μg/mL for the ethanol extract of H. macrostachys, 40.45 μg/mL for dichloromethane phase of H. macrostachys and 61.78 μg/ml for Hyptenolide. These data resulted in IC50 and CC50 resulted in a selectivity index of 1.11 for the ethanol extract of P. acuminatus; 4.68 for Justicidin B; 0.43 for the ethanol extract of H. macrostachys; 0.73 to dichloromethane phase of H. macrostachys and 2.72 to Hyptenolide. Given these results, we selected the lignan Justicidina B for further study of antileishmanial activity against L. amazonensis. In the evaluation of the DNA fragmentation pattern of L. amazonensis promastigotes, it was observed in higher concentration evaluated of Justicidin B (4x IC50) induction of DNA fragmentation similar to that observed in the positive control H2O2 (4mM). In infection model macrophage with L. amazonensis and treated with lignan Justicidin B showed reduction in both the percentage of infected macrophages as the number of amastigotes per infected macrophage, resulting in a reduction in the rate of infection compared to control, resulting decrease in the effective concentration for 50% of infection (EC50) of 9.14 and 3.58 for 24 hours and 72 hours after treatment. This result was correlated with an immunomodulatory activity of this lignan, associated with decreased levels of interleukin (IL) -10, and increased levels of nitric oxide (NO). It can be concluded that the lignan Justicidin B has significant activity antipromastigote and antiamastigote and presents immunomodulatory properties in models of infection in vitro.